2022
DOI: 10.3389/fnsyn.2022.1021832
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase-1 inhibitor-2 promotes PP1γ positive regulation of synaptic transmission

Abstract: Inhibitor-2 (I-2) is a prototypic inhibitor of protein phosphatase-1 (PP1), a major serine-threonine phosphatase that regulates synaptic plasticity and learning and memory. Although I-2 is a potent inhibitor of PP1 in vitro, our previous work has elucidated that, in vivo, I-2 may act as a positive regulator of PP1. Here we show that I-2 and PP1γ, but not PP1α, positively regulate synaptic transmission in hippocampal neurons. Moreover, we demonstrated that I-2 enhanced PP1γ interaction with its major synaptic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…By using mice with conditional deletion of the individual PP1 isoforms, we found that PP1γ is the major PP1 isoform in CA1 pyramidal neurons that is critical for synaptic transmission and LTP (Foley et al, 2022; Foley et al, 2023). We previously discovered that PP1β in CA1 pyramidal neurons plays a role opposite to that of PP1γ, in synaptic transmission, LTP induction, and memory formation (Foley et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…By using mice with conditional deletion of the individual PP1 isoforms, we found that PP1γ is the major PP1 isoform in CA1 pyramidal neurons that is critical for synaptic transmission and LTP (Foley et al, 2022; Foley et al, 2023). We previously discovered that PP1β in CA1 pyramidal neurons plays a role opposite to that of PP1γ, in synaptic transmission, LTP induction, and memory formation (Foley et al, 2023).…”
Section: Introductionmentioning
confidence: 99%